(untitled) (Acta Entomologica Serbica, 2010)
Material of the genus Ocypus Leach from the Carpathian Basin, mainly from Romania, is studied. Fourteen Ocypus species are certainly present for the Romanian fauna. Ocypus serotinus (Ádám, 1992), previously considered a nomen dubium, represents a distinct species. The male genitalia of 12 species are illustrated. A diagnostic key and a catalogue are provided for the Ocypus species of Romania. The distributions of 13 species in Romania are mapped. The distribution in the Carpathian Basin is given for Ocypus kuntzeni (G. Müller), O. tenebricosus (Gravenhorst), O. biharicus (G. Müller), O. macrocephalus (Gravenhorst) and O. ormayi (Reitter).